An optimized hydroponic pipeline for large-scale identification of wheat genotypes with resilient biological nitrification inhibition activity - Jáuregui, Iván (The New phytologist, 2023)
© 2023 The Authors. New Phytologist © 2023 New Phytologist Foundation.